Least Median of Deviance - an alternative to Maximum Likelihood Estimation in Generalised Linear Models. Application to linear logistion regression - Aishah Hamzali, Nor (Malaysian Journal of Science, 1999)
An alternative method of parameter estimation in Generalised Linear Models in the presence of outlying observations is discussed. The method, Least Median of Deviance, is an extension of the exact least median of squares for the linear regression model. A numerical example with application to logistic regression is presente